Isolated hypogonadotropic hypogonadism in adolescence: Do we need to measure the pituitary, stalk or other imaging markers? A retrospective magnetic resonance imaging study - Ayaz, Ercan; Yıldırım, Ruken; Çelebi, Canan; Özalkak, Şervan (The Turkish Journal of Pediatrics, 2023)
Background. Rapid changes in the size of the pituitary gland occur during the pubertal period. Therefore, measuring and reporting magnetic resonance imaging (MRI) in adolescents with pituitary disorders can cause unease among radiologists. Our aim was to compare the size of the pituitary gland, stalk and other previously described imaging tools in patients with isolated hypogonadotropic hypogonadism (HH) versus adolescents with a normal pituitary gland. Methods. Forty-one patients (22 female, 19 male, mean age 16.3 ±2.0 years) with HH who underwent MRI prior to starting hormone treatment were enrolled. Age, sex, and genetic mutations were noted. Pituitary height, width on the coronal plane, anteroposterior (AP) diameter on the sagittal plane, stalk thickness, pons ratio (PR), clivus canal angle (CCA) and Klaus index (KI) were measured by two radiologists twice with a one-month interval blinded to each other and patient information. Measurements were compared with the control group, including 83 subjects with normal hypothalamic-pituitary-gonadal axis and normal pituitary gland on MRI. Inter-rater and intra-rater agreements were also evaluated. Results. No significant differences were found between the two groups regarding height, width or AP diameter (p = 0.437, 0.836, 0.681 respectively). No significant differences were found between the two groups regarding CCA and PR (p = 0.890, 0.412 respectively). The KI of the male patients was significantly higher than that of the female patients and the control group (p < 0.001). The interrater agreement was moderate for pituitary height and width, poor for pituitary AP diameter and stalk thickness, good for PR and KI, and excellent for CCA. Conclusions. The measurements of the pituitary gland, stalk and posterior fossa structures were similar in adolescents with or without isolated HH. Consequently, pituitary gland, stalk or other posterior fossa measurements are unnecessary when evaluating a normal appearing pituitary gland on MRI.